THE INFLUENCE OF COMPENSATION AND WORK-LIFE BALANCE ON EMPLOYEE LOYALTY INDOMARET LHOKSEUMAWE CITY - Juliyanti; Maisyura; Nur Faliza; Nurmala (RADJA PUBLIKA, 2025)
The high employee turnover rate at Indomaret Lhokseumawe is thought to be caused by dissatisfaction with the compensation system and lack of work-life balance. This study used a quantitative approach with a survey method, involving 43 active employees from several Indomaret outlets. The results show that compensation and work-life balance have a positive and significant effect on employee loyalty. This means that the better the compensation system and the more work-life balance employees feel, the higher their loyalty to the company. The implication is that Indomaret management needs to strengthen compensation strategies and work-life balance policies in order to create a healthy, productive work environment and be able to retain employees in the long term.